Australian higher education researcher between 2020-2024 : Open-access fees, authorship, editorships, and institutional analysis. - Crawford, Joseph (Journal of University Teaching & Learning Practice v.22 n.1 p.1-15 https://doi.org/10.53761/4a3v2j43, 2025)
The Australian higher education research landscape is constantly changing, although Australia's involvement in higher education research is consistently globally ranked - often third behind the US and UK. Indeed, in some areas of higher education, Australian researchers like Boud and institutions like Deakin University rank first globally. However, less is known about the make-up of the contemporary higher education landscape (2020-2024). In this bibliometric analysis, I explore Australian authorship across 1,241 instances of authorship and 112 Australian editorship roles in the top 20 higher education journals alongside examining current ownership structures of those journals (noting other forms of publications like books, chapters, and articles outside the top 20 are much larger in volume). Editorships across the top 20 journals are also considered, noting that there are three Australian-based chief editorial appointments, and nine deputy or senior editorial appointments. Individual rankings and summaries of performance are highlighted further in this paper. I also explore current Australian institutional contributions and comment on possible pathways to increase national performance in higher education research. This paper highlights the essential role of transparency in open access fees in higher education research. [Author abstract]